2009
DOI: 10.1159/000235726
|View full text |Cite
|
Sign up to set email alerts
|

Acute Vision Loss after Intravitreal Injection of Bevacizumab (Avastin) Associated with Ocular Ischemic Syndrome

Abstract: Aim: To report a patient with diabetic rubeosis who suffered from acute retinal ischemic change and stroke after intravitreal injection of bevacizumab. Methods: A 55-year-old man had diabetes with unilateral rubeosis and macular edema. Three days after receiving intravitreal injection of bevacizumab (1.25 mg in 0.1 ml), he developed acute vision loss and change of consciousness. A complete ocular examination, fluorescein angiography, carotid artery Doppler sonography and brain magnetic resonance imaging were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…51 Rare ocular and systemic side effects There are few reports of ocular and systemic adverse events associated with intravitreal anti-VEGF agents. Rare ocular adverse events include anterior ischemic optic neuropathy after bevacizumab injection, 52,53 retinal venous occlusions after bevacizumab injection, 54 retinal artery occlusions, 55 hemorrhagic macular infarction, 56 development or exacerbation of ocular ischemic syndrome, 57 and sixth nerve palsy following bevacizumab injection. 58 Rare systemic events include formed visual hallucinations, 59 erectile dysfunction, 60 and acute decrease in kidney function.…”
Section: Methodsmentioning
confidence: 99%
“…51 Rare ocular and systemic side effects There are few reports of ocular and systemic adverse events associated with intravitreal anti-VEGF agents. Rare ocular adverse events include anterior ischemic optic neuropathy after bevacizumab injection, 52,53 retinal venous occlusions after bevacizumab injection, 54 retinal artery occlusions, 55 hemorrhagic macular infarction, 56 development or exacerbation of ocular ischemic syndrome, 57 and sixth nerve palsy following bevacizumab injection. 58 Rare systemic events include formed visual hallucinations, 59 erectile dysfunction, 60 and acute decrease in kidney function.…”
Section: Methodsmentioning
confidence: 99%
“…When patients with a past medical history of vascular obstruction such as cerebral infarction selected medical therapy, we recommended intravitreal injections of triamcinolone rather than intravitreal injections of bevacizumab because of the adverse effect of bevacizumab [8,9]. Funduscopic examinations and OCT were performed before treatment, 1 week after treatment, and every 4 weeks after treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Von Hanno et al [32] presented two cases of retinal artery occlusion after intravitreal injection of bevacizumab (Avastin) and ranibizumab (Lucentis) respectively and concluded that the therapeutic principle may be associated with an increased risk of retinal arterial occlusions. Increased risk of ocular blood flow disturbancies was noted specifically in case of bevacizumab injections-retinal venous occlusions [33] , anterior ischemic optic neuropathy [34,35] development or exacerbation of ocular ischemic syndrome [36] , decrease in retrobulbar blood flow [37] . Leung et al [38] presented a series of three patients of the nearly 200 patients with CRVO who suffered apparent macular infarction within weeks of intravitreal administration of bevacizumab.…”
Section: Impact On Ocular Blood Flowmentioning
confidence: 99%